Investigating the Drag Reduction Performance of Rigid Polymer-Carbon Nanotubes Complexes - Oluwasoga, Akindoyo Edward; Abdulbari, Hayder A. (Physics Society of Iran, 2016)
Transporting liquids in commercial Pipeline is very expensive due to cost incurred in the installation of pumping stations. This cost can be reduced by polymeric additives. However, these polymeric additives degrade over time as a result of mechanical stress the fluids are subjected to. Previous efforts to address these problems have not been successful. It is thus inevitable to find alternative means of reducing the frictional drag in fluid flow. In this present work, the experimental study of rigid polymer, Carbon Nanotubes (CNT) Nanofluids and the complex mixtures for drag reduction in a rotating disk apparatus. The finding shows that, about 50% drag reduction was achieved; a comparative study was made on the drag reduction of both complex and nanofluids, where both were able to reduce drag, however at different concentrations. It could thus be concluded that combination of xanthan gum and Carbon nanotubes could reduce drag at a particular concentration.